Humanoids for teaching and training coronary artery bypass surgery to the next generation of cardiac surgeons. (12th October 2021) - Tozzi, Piergiorgio; Ferrari, Enrico; Reuthebuch, Oliver; Matt, Peter; Huber, Christoph; Eckstein, Friedrich; Kirsch, Matthias; Mestres, Carlos A
Abstract:  : OBJECTIVES: Technical skills are an essential component of cardiac surgery, and the operating room is becoming an even more challenging environment for trainees who want to acquire such skills. Simulation, which partially overcomes this limitation, represents a valid adjunct to surgical education. We describe an original simulator and provide results in terms of trainees' evaluations and ratings. METHODS: We used a humanoid that is a silicone replica of the chest of an adult human that provides a complete anatomical platform for hands-on skin-to-skin practice of surgical techniques in arrested heart coronary artery bypass graft (CABG) surgery cases. Learners were residents in cardiac surgery. The teaching sessions included 2 full three-vessel CABG procedures using both mammary arteries and a hydrogel vein. Five board-certified cardiovascular surgeons scored the surgical activity of all trainees. The trainees were asked to complete an exit questionnaire to evaluate their course. RESULTS: Overall, 16 residents participated in the simulation, including 5 women and 11 men, with a mean age of 30 ± 4 years, all of whom had at least 2 years of cardiac surgery training. All participants completed the 2 CABG operations. Three mammary arteries (4.6%) were seriously damaged during harvesting. In 1 case (3.1%), an aortic tear occurred during aortic cannulation. Each trainee performed overall 6 distal and 2 proximal coronary anastomoses. All participants agreed that the 'humanoid reproduces real-life situations, the feeling is realistic, and they are now more confident in performing coronary anastomosis'. CONCLUSIONS: Trainees involved in this simulation curriculum acquired and refined technical skills that could be applied directly to human patients. In addition, we were able to foster a higher level of teamwork within the operating room team. Abstract : Technical skills are an essential component of cardiac surgery.